Pengembangan Modul Ajar Training Kit Instalasi Audio Video Mobil untuk Meningkatkan Hasil Belajar Praktikum Teknik Audio Video di SMK Kal-1 Surabaya - Atikah Fadhillah Alliatuzzahro; Ali Nur Fathoni; Nur Kholis; Fendi Achmad (Indo Publishing, 2026)
This study aims to develop a feasible Car Audio-Video Installation Training Kit Learning Media to address the lack of E-Module learning media in the planning and installation elements of audio-video systems, particularly for the Car Audio-Video Installation Training Kit in Grade XI Audio Video Engineering (TAV) at SMK KAL-1 Surabaya. This research employs the ADDIE development model within a Research and Development (R&D) framework. The validity of the product was assessed through material validation and media validation of the E-Module. The material validation obtained a score of 92%, while the media validation achieved 88.75%, resulting in an average score of 90%, which falls into the very valid category. Furthermore, the results of the practicality test based on student responses at SMK KAL-1 Surabaya showed a score of 88.75%, categorized as very practical. The effectiveness of the learning media was measured using the N-Gain test to determine the effectiveness of the implemented treatment. The N-Gain results for cognitive learning outcomes showed an average N-Gain score of 0.51, indicating a moderate category. This means that the learning media is effective in improving students’ learning outcomes. To compare the average pretest and posttest scores, a Paired Sample T-Test was conducted, yielding a significance value of 0.000, which indicates a significant difference. It can be concluded that the developed learning media is suitable for use in the learning process and can also serve as a reference for developing learning media in other instructional components. In the psychomotor domain, most students were able to assemble and test the Car Audio-Video Installation Training Kit correctly and in accordance with established procedures. Most students achieved a score of 88.53%, indicating that their psychomotor skills have met the Minimum Mastery Criteria (KKTP). In the affective domain, most students demonstrated good discipline, responsibility, and cooperation during the learning process and practical activities using the Car Audio-Video Installation Training Kit. Students actively followed instructions, maintained occupational safety, and respected their peers’ opinions during group discussions. Most students obtained a score of 95.47%, indicating that their affective attitudes have reached the good to very good criteria.